Manipulasi Kolaj Digital Secara Tekstual - Norliza, Mat Achim (Universiti Malaysia Sarawak (UNIMAS), 2006)
Collage means paste-up made by sticking together of paper or photographs to form artistic images. Digital collage is technique which use computer to produced an art work. "TAK NAK" is work of digital collage that use collage technique to produced an art work.